To Play While Teaching, to Teach While Playing – about Using Games and Plays during Polish Classes for Foreigners (Ludicity in (Glotto)Didactic, 2020)
Contrary to a common statement games and plays are not only for children and they are not only a form of entertainment in one’s free time. Numerous psychologists’ studies show that use of ludicity techniques in teaching supports the improvement of didactic effects. The article presents the results of a questionnaire survey carried among people learning Polish as a foreign language and their lecturers. They show how they interpret particular ludicity elements.